Hydroxychavicol as an antifungal agent : effects on trichophyton rubrum and cytotoxicity - Muhd Ridzuan Pauzi
Trichophyton rnbrum is one of the most prevalent dermatophytes causing both local and systemic infection. Current available antifungal agents may cause severe side¬effects and emergence of resistant strains. Hydroxychavicol (HC) is an active compound of Piper leaf species. It has been reponed to have antifungal properties against dermatophytes including T rubrum. The properties of HC and its mechanisms of action as an antifungal agent against 7: rubrum has not been comprehensively explained. Hence this study is aimed to identify the effects of HC as an antifungal agent against 7: rubrum. Broth dilution method was used to determine the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) of HC against T rubrum (ATCC 28188). The morphology of T rubrum was then studied using transmission electron microscope (TEM). On the other hand, fungal cytoskeletal enzymes (chitin synthase) gene expressions were evaluated using real-time PCR. Subsequently, cytotoxicity studies using human dermal fibroblast (HDF) and pre-adipocyte (3T3-L I) cell lines were performed by means of MTT cell proliferation assay. The level of MIC and MFC of the HC against 7: rubrum was 0.491lg/mL. Subsequently, microscopic study revealed significant destruction of the fungal organelles and cell wall. The fungal cytoskeletal enzyme (chitin synthase) gene expressions showed upregulated at Day-I and down regulated from Day-5 until Day-7 of treatment. On the other hand, HC was less toxic when compared to rniconazole as the reference antifungal agent to the tested cell lines (HDF and 3T3-Ll). Administration ofHC led to 7: rubrum cell wall distruption and organelles destruction as well as changes in the expression of the chitin synthase gene. Hence, HC could potentially be used as an alternative therapeutic agent against T rnbrum infections.